Peningkatan kekerasan dan ketahanan korosi paduan Fe-2,9Al-0,4C dengan proses karburisasi padat - Kartikasari, R.; Susiana, A.; Ocktavian, D. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2021)
Fe-Al-C alloy is a superior and economical new alloy to replace the ferritic stainless steel, whereas aluminum replaces chromium, which is relatively expensive. Some applications of Fe-Al-C alloys require hardness at the surface. This study aims to determine the effect of the temperature carburizing process on the hardness and corrosion resistance of Fe-2,9Al-0,4C alloys. Material used is Fe-2,9Al-0,4C steel alloy. Surface hardening using a solid carburizing method. The solid carburizing process carried out by the holding time for 3 hours at various temperatures of 850°C, 900°C, 950°C, 1000°C, and 1050°C. Carburized is used in the form of powder coal and MgCO3 catalyst. Tests carried out are chemical composition, microstructure, hardness, and corrosion tests. The test results show that the chemical composition of the Fe-2,9Al-0,4C alloy contains elements of 2.91% Al and 0.40% C. Microstructure formed is ferrite and pearlite with a dendritic pattern. The martensitic structure formed at 950°C, 1000°C, and 1050°C. The Carburizing process increases the hardness value where the higher temperature carburizing process, the higher hardness values until it reaches a maximum temperature of 1050°C with a hardness value of 1040.5 kg/mm2. The highest corrosion resistance value occurs after the 850°C carburizing process at a rate of 41.58 mpy corrosion (up 40.9% of the raw material). At a higher temperature carburizing process lowers the corrosion resistance of the alloy Fe-2,9Al-0,4C.